A rostral neurovascular system in the mosasaur Taniwhasaurus antarcticus - Alvarez Herrera, Gerardo Paulino; Agnolin, Federico; Novas, Fernando Emilio (The Science of Nature)
Mosasaurs were a cosmopolitan group of marine squamate reptiles that lived during the Late Cretaceous period. Tylosaurinae mosasaurs were characterized for having an edentulous rostrum anterior to the premaxillary teeth. External morphology of the snout of the tylosaurine Taniwhasaurus antarcticus from the Upper Cretaceous beds at James Ross Island (Antarctic Peninsula) shows a complex anatomy with diverse large foramina and bone sculpture. A computed tomography scan of the Taniwhasaurus rostrum revealed a complex internal neurovascular system of branched channels in the anteriormost part of the snout. Systems like this are present in extant aquatic vertebrates such as cetaceans and crocodiles to aid them with prey detection, and are inferred to have functioned in a similar manner for several extinct reptile clades such as plesiosaurs and ichthyosaurs. Thus, it is probable that Taniwhasaurus also was able to detect prey with an enhanced neural system located in its rostrum. This condition may be more widespread than previously thought among mosasaurs and other marine reptiles. Fil: Alvarez Herrera, Gerardo Paulino. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Agnolin, Federico. Universidad Maimónides; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Novas, Fernando Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina